Relationship between cephalometric cranial base and anterior-posterior features in an Iranian population - Mohammad Monirifard; Saeid Sadeghian; Zahra Afshari; Elahe Rafiei; Asana Vali Sichani (Wolters Kluwer Medknow Publications, 2020)
Background: The relationship between the dimensions of the cranial base and skeletal anterioposterior problem has been controversial for years. The aim of this study was to determine the relationship between the anterioposterior cephalometric indicators and the cranial base cephalometric indicators in an Iranian population. Materials and Methods: In this historical cohort cephalograms of 100 skeletal Class I patients, 101 skeletal Class II patients, and 98 skeletal Class III patients were selected. The cephalograms were traced manually and the indicators were measured. Finally, data were analyzed by SPSS software using the Mann-Whitney test and Pearson's correlation test. The significance level was set at 0.05. In cases that the correlation coefficient (r) was 0.6 or higher, linear regression was used. Results: The dimensions of the cranial base are significantly larger in men than that in women. Anterior cranial base length (SN) showed statistically significant difference between Class I and Class II groups (P < 0.05). BaSN, ArSN, and SN-FH showed statistically significant differences between Class II and Class III groups (P < 0.05). Conclusion: Smaller cranial base angle in the skeletal Class III malocclusion compared to skeletal Class II malocclusion has been demonstrated in this study. A significant correlation between the cranial base angle, the cranial base dimension, and the effective length of the maxilla was observed, and the smaller cranial base angle in Class III malocclusion was also confirmed. These findings indicate that the cranial base can affect the development of maxilla and mid-face.